Geography for 11-14 years - Robinson, Stephanie (Curriculum for Wales, 2022)
Embodying the aims of the new curriculum for Wales, and forming part of the Humanities Area of Learning and Experience, Curriculum for Wales: Geography for 11-14 years will help you plan your curriculum, offering 18 chapters packed full of geographical resources, including maps, charts, diagrams and data. >> Build students' curiosity about the world around them - how it developed, what it is like now, and what it could be like in the future by helping you develop an enquiry-based approach to learning. >> Explore geography at a local, national and global scale and foster students' sense of cynefin with a focus on Wales and its place on the wider world. >> Develop core geographical skills with fieldwork enquiries embedded into the context of topics, encouraging students to investigate their local area. >> Support teachers in planning and assessment with suggested learning objectives. >> Help students to consider topics in the context of their own lives and the local area in which they live with regular 'My place' activities. >> Encourage students to think about the impact of human actions in their local area, on Wales and the world, to develop ethical informed citizens. >> Choose from crucial content areas including: weather and climate; ecosystems; landscapes and national parks; rural and urban places; sport and culture; climate change; disease; global consumers and more.